An experimental study on packing and drift eliminators in an evaporative condenser with induced draft - Mohiuddin, A. K. M.; Kant, Keshav; Sen, Subroto (Council of Scientific & Industrial Research, 1992)
The pressure drop and drift loss characteristics of cement asbestos dift eliminators (CADE), concrete drift eliminators (CDE) and cellular type drift eliminators (CTDE) in an evaporative condenser (EC) were experimentally investigated. For CADE and CDE, data were taken for various number of stages, n and for a range of the orientation angle,theta of the eliminator plates. For CTDE, the data were recorded for various values of n and the air velocity through a drift eliminator stage. The results showed that the pressure drop and drift were strong function of n and air flow rate. In case of CADE and CDE, they were strongly dependent on theta as well. A cellular type packing placed inside the EC was also studied experimentally ans its volume transfer coefficient was correlated in terms of the ratio of liquid to air loading.